Biatrial Cardiac Metastases in a Patient with Uterine Cervix Malignant Melanoma - Caglayan Geredeli; Melih Cem Boruban; Necdet Poyraz; Mehmet Artac; Alpay Aribas; Lokman Koral (Case Reports in Cardiology)
Primary malignant melanomas of uterine cervix are quite rarely seen neoplasms, and long-life prognosis of patients with this disease is poor. Immunohistochemical methods and exclusion of other primary melanoma sites are used to confirm the diagnosis. As with other melanomas, cervix malignant melanomas may also cause cardiac metastases. Cardiac metastases are among rarely seen but more commonly encountered cases, compared to primary cardiac tumors. Here, we present a case of biatrial cardiac metastases in a 73-year-old patient with uterine cervix malignant melanomas. The patient underwent echocardiography, cardiac magnetic resonance imaging, and computed tomography. Our report shows the importance of advanced diagnostic techniques, such as cardiac magnetic resonance, not only for the detection of cardiac masses, but for a better anatomic definition and tissue characterization. Although the cases of malignant melanomas leading to multiple cardiac metastasis were reported in literature, the metastatic concurrence of malignant melanomas in both right and left atriums is quite rarely encountered as metastatic malignant melanomas. Also, another intriguing point in our case is that the primary lesion of our case was stemmed from uterine cervix, but not skin.